Osteoarticular Involvement-Associated Biomarkers and Pathways in Psoriasis: The Shared Pathway With Ankylosing Spondylitis - Zhang, Yu-Ping; Wang, Xing; Jie, Li-Gang; Qu, Yuan; Zhu, Xiao-Tong; Wu, Jing; Yu, Qing-Hong (Frontiers in Immunology, 2022)
Abstract Objectives:Psoriatic arthritis (PsA) is a unique immune-mediated disease with cutaneous and osteoarticular involvement. However, only a few studies have explored the susceptibility of osteoarticular involvement in psoriasis (Ps) at the genetic level. This study investigated the biomarkers associated with osteoarticular participation and potential shared molecular mechanisms for PsA and Ankylosing Spondylitis (AS). Methods: The RNA-seq data of Ps, PsA and AS in the Gene Expression Omnibus (GEO) database were obtained. First, we used the limma package and the Weighted Gene Co-Expression Network Analysis (WGCNA) to identify the potential genes related to PsA and AS. Then, the shared genes in PsA and AS were performed using the GO, KEGG, and GSEA analyses. We also used machine learning to screen hub genes. The results were validated using external datasets and native cohorts. Finally, we used the CIBERSORT algorithm to estimate the correlation between hub genes and the abundance of immune cells in tissues. Results: An overlap was observed between the PsA and AS related modules as 9 genes. For differentially expressed genes in AS and PsA, only one overlapping gene was found (COX7B). Gene enrichment analysis showed that the above 9 genes might be related to the mRNA surveillance pathway. The GSEA analyses showed that COX7B was involved in adaptive immune response, cell activation, etc. The PUM1 and ZFP91, identified from the support vector machine, had preferable values as diagnostic markers for osteoarticular involvement in Ps and AS (AUC>0.7). Finally, CIBERSORT results showed PUM1 and ZFP91 involvement in changes of the immune microenvironment. Conclusion: For the first time, this study showed that the osteoarticular involvement in psoriasis and AS could be mediated by the mRNA surveillance pathway mediated abnormal immunologic process. The biological processes may represent the crosstalk between PsA and AS. Therefore, the PUM1 and ZFP91 could be used as potential biomarkers or therapeutic targets for AS and Ps patients.